Long-term observations of aerosol optical depths at the Meteorological Observatory Lindenberg - Michael Weller; Klaus Gericke (Meteorologische Zeitschrift, 2005)
The Meteorological Observatory Lindenberg operates a monitoring transect for routine measurements of aerosol optical depth (δA) across Germany from the Baltic Sea to the Alps, which includes the stations Zingst, Lindenberg, Hohenpeißenberg and the Zugspitze. The paper presents mainly results retrieved from the δA-time series of Lindenberg (since 1986), complemented by some results based on the Hohenpeißenberg-δA-time series (since 1994). It is shown that the aerosol optical depth decreases uniformly (interrupted by the Pinatubo event) from 1986 to 2005. The total particle number decreases and the real part of the refractive index of the atmospheric aerosols of the lower troposphere starts to shift towards higher values after 1998. Distinct differences exist for δA-spectra and the column related aerosol parameters retrieved from them between the German lowland (Lindenberg) and the German highland (Hohenpeißenberg). This illustrates the influence of low-tropospheric aerosols on optical properties of the total atmospheric column. Further, the significance of reliable ground measurements for the validation of satellite products is demonstrated. This reflects the high value of long-time observations as routinely conducted at the Meteorological Observatory Lindenberg.